2017
DOI: 10.1186/s12936-017-1952-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-falciparum malaria imported mainly from Africa: a review from a Portuguese hospital

Abstract: BackgroundNon-falciparum malaria (NFM) has been reported to be responsible for around 25% of imported malaria cases in Europe but is often neglected due to its less severe clinical course when compared to Plasmodium falciparum. Differentiation between species is however crucial for a correct approach. The objective of this study is to report the cases of this often missed aetiology of malaria in a tertiary hospital in Portugal.MethodsData were retrospectively analysed from patients admitted from January 2006 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
1
20
0
2
Order By: Relevance
“…were identified with a possible 3 additional cases identified as P. ovale spp. or P. vivax [15]. Additional cases have been described in Latin America, most frequently in the context of travel to Africa and until recently, relied solely upon microscopy [29–31].…”
Section: Resultsmentioning
confidence: 99%
“…were identified with a possible 3 additional cases identified as P. ovale spp. or P. vivax [15]. Additional cases have been described in Latin America, most frequently in the context of travel to Africa and until recently, relied solely upon microscopy [29–31].…”
Section: Resultsmentioning
confidence: 99%
“…Among the 40 articles included in the review, 3 reported on Pk [ 22 , 29 , 43 ], 8 on Pm [ 13 , 19 , 21 , 23 , 27 , 32 , 38 , 39 ], 5 on Po [ 23 , 25 , 30 , 31 , 54 ], 1 on Pk and Pm [ 32 ], and 23 on Pm and P o [ 24 , 26–28 , 33 , 35–39 , 41 , 45–47 , 49–52 , 55–58 , 61 ]. The majority of studies (n = 23) were done in nonendemic settings using samples obtained from imported cases (international travellers or migrants) [ 23 , 24 , 26 , 28 , 30 , 33 , 35–39 , 45 , 47 , 49–52 , 54–58 , 61 ]. Sixteen studies were conducted in endemic settings [ 22 , 25 , 29 , 31 , 32 , 34 , 40–44 , 46 , 48 , 53 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The highest sensitivity reported was 80% (95% CI, 28%–99%), as estimated by evaluating 5 Pm cases [ 53 ]. Specificities of type 2 RDTs as reported in seven studies ranged 42%–99% [ 27 , 28 , 45 , 47 , 53 , 58 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aedes aegypti e Aedes albopictus 27,10,49,38,45 . O aumento exagerado da dengue nos últimos 50 anos deve-se a vários fatores, como o aumento da população, movimentos emigratórios e migratórios, fontes de água contaminadas e prevenção ineficiente ou insustentável 10 .…”
Section: Dengueunclassified